(2x-1)(x-13)=

Simple and best practice solution for (2x-1)(x-13)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x-1)(x-13)= equation:


Simplifying
(2x + -1)(x + -13) = 0

Reorder the terms:
(-1 + 2x)(x + -13) = 0

Reorder the terms:
(-1 + 2x)(-13 + x) = 0

Multiply (-1 + 2x) * (-13 + x)
(-1(-13 + x) + 2x * (-13 + x)) = 0
((-13 * -1 + x * -1) + 2x * (-13 + x)) = 0
((13 + -1x) + 2x * (-13 + x)) = 0
(13 + -1x + (-13 * 2x + x * 2x)) = 0
(13 + -1x + (-26x + 2x2)) = 0

Combine like terms: -1x + -26x = -27x
(13 + -27x + 2x2) = 0

Solving
13 + -27x + 2x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(1 + -2x)(13 + -1x) = 0

Subproblem 1

Set the factor '(1 + -2x)' equal to zero and attempt to solve: Simplifying 1 + -2x = 0 Solving 1 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -2x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -2x = 0 + -1 -2x = 0 + -1 Combine like terms: 0 + -1 = -1 -2x = -1 Divide each side by '-2'. x = 0.5 Simplifying x = 0.5

Subproblem 2

Set the factor '(13 + -1x)' equal to zero and attempt to solve: Simplifying 13 + -1x = 0 Solving 13 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + -1x = 0 + -13 Combine like terms: 13 + -13 = 0 0 + -1x = 0 + -13 -1x = 0 + -13 Combine like terms: 0 + -13 = -13 -1x = -13 Divide each side by '-1'. x = 13 Simplifying x = 13

Solution

x = {0.5, 13}

See similar equations:

| 4(y-2)=10-2y | | 0=6a+48 | | 11n^2-7n-2=-6+8n^2 | | 3(x+9)=2x-6 | | 9(-24)-5((-24)-8)= | | 7.5x+3.3-2x-6.7= | | Axb=A+13-b | | x+7.72=963 | | 4x+7=2x-15 | | -4-3z=23 | | (3i)-(6i)=0 | | 7=8y-17 | | 3(b+3)=42 | | (x^2)-x+400=0 | | 2(a-3)=40 | | 0.34=lnx | | 6x-1=125 | | 2+x+3x=34 | | y=x(x-2y)+2y(x+2y) | | -4x^2+11x-6=o | | (x^2)-x+20=0 | | 16q-18=qr+t | | 5x+6-x=-30 | | 0.5x+7=-9 | | G-24=14 | | x^3-12x^2+230.4=0 | | 25+4y=25+16 | | 5x-3(x-3)=4+5x-8 | | 0.5x+6=17 | | -4(6x-7)=-24x-28 | | -12x-65=-7x | | 5-(2x+2)=-(-3x+5)-x |

Equations solver categories